1989
DOI: 10.1101/gad.3.12b.2180
|View full text |Cite
|
Sign up to set email alerts
|

An ordered pathway of assembly of components required for polyadenylation site recognition and processing.

Abstract: Four HeLa cell nuclear factors that are required for specific pre-mRNA cleavage and polyadenylation have been extensively purified, thereby permitting an investigation of the role of each in the 3' processing reaction. Two factors, termed PF1 and PF2, are required for specific polyadenylation of the cleaved RNA. PFI is a poly(A) polymerase, and PF2 is a factor that confers AAUAAA specificity to the reaction. Both of these factors, along with two additional factors termed CF1 and CF2, are required for the endon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

10
201
2

Year Published

1991
1991
1992
1992

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 188 publications
(213 citation statements)
references
References 35 publications
10
201
2
Order By: Relevance
“…Fig. 2 also shows that the DE150 fraction from the first step in the purification of polyadenylation factors (Gilmartin and Nevins, 1989) is able to use ADP efficiently for poly(A) addition to a probe containing the AAUAAA sequence element (lanes I), but not the mutated AACAAA sequence element (lanes 2). In contrast, the DE150 fraction catalyzes the ATP-supported polyadenylation of the AAUAAA probe only weakly (Fig.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…Fig. 2 also shows that the DE150 fraction from the first step in the purification of polyadenylation factors (Gilmartin and Nevins, 1989) is able to use ADP efficiently for poly(A) addition to a probe containing the AAUAAA sequence element (lanes I), but not the mutated AACAAA sequence element (lanes 2). In contrast, the DE150 fraction catalyzes the ATP-supported polyadenylation of the AAUAAA probe only weakly (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Lack of a specific ATP-dependent poly(A) addition reaction in the DE150 fraction (McDevitt et al, 1988;Gilmartin and Nevins, 1989), or in similar first-step purification fractions (Christofori and Keller, 1988;Takagaki et al 1988;Bardwell et al, 1990) has been reported previously. It is well established that the poly(A) addition reaction assayed with ATP requires a non-specific poly(A) polymerase (Christofori and Keller, 1989;Gilmartin and Nevins, 1989;Bardwell et al, 1990) and at least one, and possibly several, additional factors which recognize the AAUAAA sequence element (Christofori and Keller, 1988;Takagaki et al, 1988;Gilmartin and Nevins, 1989). To test if the ADP-dependent poly(A) addition reaction also requires multiple components, the crude nuclear extract was fractionated on a 15-35% glycerol gradient and the fractions were recombined and assayed for ADP-and ATP-supported polyadenylation.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations